The nexus between e-commerce growth and solid-waste emissions in china: Open the pathway of green development of e-commerce - Caiyi, Liang; Xiaoyong, Li; Zhenyu, Liu (Frontiers in Environmental Science, 2022)
The growth of the e-commerce industry brings considerable waste. The Chinese government has begun to pay attention to the development of green e-commerce. We first analyze the nexus between China’s e-commerce industry and solid waste and hope to provide some insights into the development of green e-commerce. Considering the cross-sectional dependence of panel data, we adopt the second-generation panel unit root and cointegration tests. Furthermore, the empirical results from the DOLS show that the EKC quadratic curve exists in Whole & Eastern & Central & Western China. In Whole & Central & Western China, FDI will increase solid-waste emissions. In Central China, the market can significantly increase solid-waste emissions, and trade openness can reduce solid-waste emissions. The proportion of Eastern China’s secondary industry will substantially increase solid-waste emissions. Most of the eight major economic zones conform to the quadratic EKC curve except for three economic zones. The situation is as follows, In the Middle Reaches of the Yellow River, the development of e-commerce brings monotonically increasing solid-waste discharge. The EKC relationship does not exist in the Yangtze River’s middle reaches and Northwest Economic Zones. Research findings provide a perspective and basis for China to make regional green regulations to reduce the discharge of solid waste from e-commerce and open the pathway of green development of e-commerce.